(untitled) (Fiep Bulletin - online, 2014)
The purpose of this study descriptive character, with a transversal cut,is to classify the prevalence of overweight and obesity in schools based on different tables of reference used by Brazilian researchers, a Regional table prepared for the Rio Grande do Norte, proposed for the study. The study design has a and involves a sampling of 2363 Basic Education schools (2nd to 9th grades), In both genders with ages ranging from 6 to 15 years, in the public school system, in the state of Rio Grande do Norte, that were selected in a stratified form. The measuring instruments used were: the Filizola Scale (wieght); a Sanny metric devise (height), having as reference criteria the NCHS2000, the Monteiro 2006 and the Cole et al2000. Critical values were presented for the measurement of low weight (LW), overweight (OW) and obesity (OB), where The results point to the prevalence of overweight and obesity as being less than the criteria established in the CDC (2000), Conde, Monteiro (2006) or the Cole et al(2000) for both sexes. Thus, the data found in this study provide evidence that the results differ according to the normative table adopted. The CMI values for the population of Rio Grande do Norte were found to be overestimated when international tables were used, since they have cut off points that are lower than the table proposed by this study.